A density functional theory study on multiple exciton generation in lead chalcogenides - Nur Farha, Shaafi; Saifful Kamaluddin, Muzakir; Mohd Fakhrul Zamani, Kadir; Shujahadeen, B. Aziz (Taylor & Francis, 2020)
Quantum confined structure-based solar cell is promising two folds increment of the maximum theoretical photovoltaic conversion efficiency i.e., > 60% in comparison with that of the bulk analogs e.g., silicon-based and dye sensitized solar cell (ca. 32% of maximum theoretical efficiency). The key to the significant increment is the ability of the fluorophore to exhibit multiple exciton generation upon absorption photon with sufficient energy. Small size of lead chalcogenides (PbS, PbSe, PbTe) crystals have been reported and proven experimentally could exhibit this unique property. We have investigated few clusters of narrow bandgap lead chalcogenides nanocrystals i.e., (PbS)n, (PbSe)n and (PbTe)n; which n¼4 - 80. The cluster models were optimized using quantum chemical calculations to the lowest energy geometry at B3LYP/lanl2dz level of theory. The predicted realistic (PbS)80, (PbSe)50, and (PbTe)74 clusters with the size, and bandgap of 4.58 nm (2.00 eV), 4.03nm (1.51 eV), and 4.84nm (1.55 eV) are smaller than that of their exciton Bohr radius i.e., 5.01, 13.1, and 24.8 nm respectively. Therefore, the occurrence of multi exciton generation in the clusters is hypothesized upon absorption of photon with Ephoton ¼ 2Eg.